Placenta-Eating and the Epistemology of Ignorance - Heyes, Cressida (Atlantis, 2016)
This article argues that human postpartum placentophagy—eating one’s placenta—is an example of an epistemology of ignorance. Placentophagy has been stubbornly resistant to conventional scientific inquiry, but has nonetheless been the subject of considerable epistemic speculation based on very little evidence. To remain ignorant about placentophagy takes epistemic work. Tracing the form the epistemology of ignorance takes—disdain for female bodies, visceral disgust—this article argues that placentophagy deserves a more nuanced treatment as a practice that meets the under-served needs of women who fear postpartum depression and as a practice taking place in a context of the biomagnification of environmental pollutants.